Peptidyl Arginine Deiminase 4: APromising Therapeutic Target in Rheumatoid Arthritis and Other Diseases (Asian Journal of Pharmaceutics (AJP), 2025)
The present review offers comprehensive data on the roles of Peptidyl Arginine Deiminase 4 (PAD4) in variousdiseases, including rheumatoid arthritis (RA). PAD4, an enzyme responsible for converting arginine to citrulline,has been linked to the development of chronic inflammation. The current study is a narrative review to determinewhether PAD4 is a potential therapeutic target for RA and other illnesses. We searched PubMed and GoogleScholar for studies published before 2024. The potential therapeutic utility of PAD4 in various diseases such ascancer, miscarriage, multiple sclerosis, retinopathy, and RA is emphasized in the article. This paper explores theadvancements in the development of small-molecule inhibitors and monoclonal antibodies targeting PAD4. Itstresses the importance of conducting additional research to resolve specificity, safety, and sustained effectivenessconcerns. The review emphasizes the need for a comprehensive approach to completely comprehend the variedattributes and potential therapeutic applications of PAD4.